Review of The Peculiar Revolution: Rethinking the Peruvian Experiment under Military Rule, edited by Carlos Aguirre and Paolo Drinot - Kruijt, Dirk (European Review of Latin American and Caribbean Studies, 2018)
The Peculiar Revolution: Rethinking the Peruvian Experiment under Military Rule, edited by Carlos Aguirre and Paolo Drinot. University of Texas Press, 2017.